Audiometric profile of civilian pilots according to noise exposure - Taiana Pacheco Falcão; Ronir Raggio Luiz; Gabriel Eduardo Schütz; Márcia Gomide da Silva Mello; Volney de Magalhães Câmara (Universidade de São Paulo, 2014)
OBJECTIVE To evaluate the audiometric profile of civilian pilots according to the noise exposure level. METHODS This observational cross-sectional study evaluated 3,130 male civilian pilots aged between 17 and 59 years. These pilots were subjected to audiometric examinations for obtaining or revalidating the functional capacity certificate in 2011. The degree of hearing loss was classified as normal, suspected noise-induced hearing loss, and no suspected hearing loss with other associated complications. Pure-tone air-conduction audiometry was performed using supra-aural headphones and acoustic stimulus of the pure-tone type, containing tone thresholds of frequencies between 250 Hz and 6,000 Hz. The independent variables were professional categories, length of service, hours of flight, and right or left ear. The dependent variable was pilots with suspected noise-induced hearing loss. The noise exposure level was considered low/medium or high, and the latter involved periods > 5,000 flight hours and > 10 years of flight service. RESULTS A total of 29.3% pilots had suspected noise-induced hearing loss, which was bilateral in 12.8% and predominant in the left ear (23.7%). The number of pilots with suspected hearing loss increased as the noise exposure level increased. CONCLUSIONS Hearing loss in civilian pilots may be associated with noise exposure during the period of service and hours of flight.